1982
DOI: 10.1128/iai.35.1.256-263.1982
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estradiol and progesterone on Bacteroides melaninogenicus and Bacteroides gingivalis

Abstract: Bacteroides melaninogenicus subsp. intermedius increases in the subgingival microflora during pregnancy. These studies evaluated direct interactions between hormonal steroids and oral Bacteroides species. Resting cell suspensions of pure cultures of plaque organisms were incubated anaerobically with [14C]estradiol and [14C]progesterone. Uptake of labeled compound per microgram of bacterial protein was determined by thin-layer chromatography and liquid scintillation counting. B. melaninogenicus subsp. intermedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
147
0
8

Year Published

1991
1991
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(162 citation statements)
references
References 32 publications
(15 reference statements)
7
147
0
8
Order By: Relevance
“…melaninogenica and Pr. intermedia, but not P. gingivalis can substitute estradiol and progesterone for their vitamin K requirement [24]. The uptake of these compounds is also influenced by addition of fumarate, suggesting a role for steroids in the electron transport system of these species.…”
Section: Lipid Metabolismmentioning
confidence: 93%
“…melaninogenica and Pr. intermedia, but not P. gingivalis can substitute estradiol and progesterone for their vitamin K requirement [24]. The uptake of these compounds is also influenced by addition of fumarate, suggesting a role for steroids in the electron transport system of these species.…”
Section: Lipid Metabolismmentioning
confidence: 93%
“…Microorganisms of the dental plaque may also react specifically to increased availability of hormones in oral fluids. Such effects have been described, e.g., estradiol may be utilized by Bacteroides spp, (Kornman & Loesche 1982) and may substitute for menadione, an important growth factor for black-pigmenting Bacteroides (BPB) (Gibbons & Macdonald 1960). Gram-negative anaerobic bacteria including BPB are frequently found in diseased periodontal sites (Slots 1982, Zambon et al 1981, Dzink et al 1985 and species of this group of organisms are considered to be an important part of the presumptive pathogenic flora.…”
mentioning
confidence: 99%
“…A similar increase in the number of B. intermedius has been reported in pregnant women and in women taking oral contraceptives [44,45]. It has been suggested that sex hormones may act as growth factors for Bacteroides species [46]. In many studies, black-pigmented Bacteroides species have been associated with periodontal disease [471.…”
Section: Andmentioning
confidence: 56%